Protectionist responses to the crisis – global trends and implications - Matthieu Bussière; Emilia Pérez-Barreiro; Roland Straub; Daria Taglioni (European Central Bank (ECB), 2010)
In this paper we take a systematic look at recent trends in global protectionism and at the potential implications of a protectionist backlash for economic growth, using results from the recent economic literature and new model simulations. We find that there has so far been a moderate increase in actual protectionist measures to restrict trade through tariff and non-tariff barriers. At the same time, evidence from surveys shows that public pressure for more economic protection has been mounting since the mid-2000s, and has possibly intensified since the start of the financial crisis. However, no World Trade Organization (WTO) member has retreated into widespread trade restrictions or protectionism to date. Our model-based simulations suggest that the impairment of the global flow of trade would hamper the recovery from the crisis, as well as the long-term growth potential of the global economy. At the same time, it is unlikely that protectionism would help to correct existing current account imbalances. Moreover, the countries implementing protectionist measures should expect a deterioration of their international competitiveness, which would further affect the potential for longer-term real GDP growth.
Keywords: E22; E50; 330; competitiveness; financial crisis; global imbalances; Protectionism; Trade; World Trade Organization